Anfibios de una reserva natural del departamento Las Colonias, provincia de Santa Fe, Argentina - Demartin, Rocio Pamela (2020)
In this work, we report the amphibian fauna composition of a natural protected area locatednear Esperanza city, Province of Santa Fe, Argentina. It opened to the public in 2015, with yetno baseline inventory of amphibian species. Additionally, we evaluated the presence of the amphibianparasitic fungus Batrachochytrium dendrobatidis (Bd). We carried out eleven samplingsfrom October 2015 to March 2016 in three environmental units: native forest, exotic forest,and floodplain grasslands. The sampling methods we used were live pit-fall traps with driftfences, auditory encounters, and visual encounters. Sixteen species belonging to 9 genera and4 families were recorded. October was the month with the highest specific richness. Bd-specificreal-time Taqman qPCR made on skin swabs made on 11 species were all negative. Even small,the amphibian species identified in the protected area represent ca. 30% of the anurans alreadyreported for Santa Fe, and 9% of the Argentinean batracofauna.